Efforts To Control Hypertension and Diabetes Mellitus Through “SEGER WARAS” Community Visits and the “PINTAR” Calendar in Nguter District - Sunardi; Yudied Mirasa; Moh. Alimansur (Journal of Community Engagement in Health, 2026)
Hypertension and diabetes mellitus are major non-communicable diseases that continue to increase and contribute significantly to morbidity and mortality, particularly in low- and middle-income countries. In the working area of Nguter Primary Health Center, the achievement of standard health services for hypertension and diabetes mellitus has not yet met the Minimum Service Standards. This community engagement activity aimed to improve early detection, community knowledge, and medication adherence through innovative programs, namely the “SEGER WARAS” community visit program (blood pressure and blood glucose screening for healthy citizens) and the “PINTAR” calendar (intensive blood pressure monitoring and routine blood glucose management). The methods included problem identification using health center performance data and interviews, priority setting using the Urgency, Seriousness, and Growth (USG) method, and implementation of screening, education, and community assistance activities. The results showed increased community participation in screening activities, identification of new hypertension and diabetes cases, improved knowledge regarding disease management, and better adherence to routine medication. These programs demonstrate potential as sustainable community-based strategies to strengthen non-communicable disease control at the primary health care level.